Smartphones and their role in the modern classroom - Mammadova, Tamilla (Revue internationale des technologies en pédagogie universitaire / International Journal of Technologies in Higher Education)

(untitled) (CRIFPE, 2018)
Mobile and wireless technologies have reached such a high level of sophistication that, today, they can be more easily incorporated into teaching and learning processes. The purpose of this paper is to examine the extent to which present-day classes can benefit from the use of smartphones and mobile applications. To this end, a study looked at the experience of 204 ADA University students in the Faculty of General Education over two academic terms in a Writing and Information Literacy course. At the end of the academic year, the students filled out a survey. Descriptive statistics, such as simple percentage mean and standard deviation, were used to analyze the data. The study reveals that smartphone functions like note-taking, photos of the whiteboard and/or smartboard, video recordings, and the WhatsApp application can become an integral part of the modern classroom. The study also suggests that smartphone technology should be widely applied by university teachers/instructors and, in the future, may lead to certain changes in teaching methodology generally.